Forms and Meaning of Laku Prihatin for Javanese Women in Ngadi Sarira Tradition - Roudhotul Munawaroh; Titis Srimuda Pitana; Warto Warto (International Journal of Science and Applied Science: Conference Series, 2022)
The philosophy of the Javanese women’s beauty trilogy, namely ngadi sarira, ngadi busana, and unggah-ungguh (manners) displays an attractive image for Javanese women. Education about traditional beauty care procedures for Javanese women can be seen through a tradition called ngadi sarira. Actually, what is the uniqueness of Javanese women in terms of beauty and self care? Based on the concept of beauty in the style of the princess of the Surakarta Sultanate Palace, this study tries to reveal 1) The forms of laku prihatin performed by Javanese women in the ngadi sarira tradition, and 2) The meaning of laku prihatin for Javanese women in the ngadi sarira tradition. This research is a qualitative research using Clifford Geertz’s theory of interpretation of meaning. This study aims to review the forms and meanings of caring behavior to obtain the beauty of the female body from inside and outside in the ngadi sarira tradition. The results showed that the forms of laku prihatin performed by Javanese women in the ngadi sarira tradition, namely ngudhup mlathi, mutih, adus bengi, and turu sepisan. The meaning of inner beauty, religious meaning, ritual meaning, and economic meaning.